The Effect of Load and Stress on Work Performance with Motivation as a Moderation Variable (Case Study at the Ministry of Religious Affairs of the Republic of Indonesia) - Dian Anggraeni Rahim; Asep Sjafrudin; Dewi Prafitaningrum (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to analyze the effect of burden and stress on the work performance ofemployees of the Ministry of Religious Affairs of the Republic of Indonesia with motivationas a moderation variable. One of the main duties of the Ministry of Religious Affairs of theRepublic of Indonesia is to provide services to the community related to education in thelevel of kindergarten to university in Indonesia. Given the large work area of employees andthe heavy workload in the ministry, it is not uncommon for employees to lose motivation atwork, that makes the achievement is low. 97 employees were involved in this study. Usingthe SEM-PLS method, the results of this study show that the indicator reliability, Cronbachalpha, composite reliability and AVE values are valid. The discriminant validity value isgreater than the factor charge value. Workload negatively influences work performanceeither directly or indirectly, moderated by motivation. Work stress positively influenceswork performance directly or indirectly, moderated by motivation. Motivation has a positiveinfluence on work performance.